JUMPA Vol.2 No.3 Okt 2015 FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PENGETAHUAN YANG DIALIHKAN PADA PERUSAHAAN MULTINASIONAL DI JAKARTA: FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PENGETAHUAN YANG DIALIHKAN PADA PERUSAHAAN MULTINASIONAL DI JAKARTA - Setyani Dwi Lestari Universitas Budi Luhur (Jurnal Manajemen dan Perbankan (JUMPA), 2015)
This study aims to obtain empirical evidence about the influence of resource complementarity, operational compatibility dan cultural compatibility to interorganizational learning and relational capital, also affect to quality of knowledge transferred. Sample consisted of 110 top management team of companies. Questionnaires distributed 110 questionnaires, and 110 questionnaires distributed back that can be processed as many as 110 questionnaires. processing using the test validity, reliability testing, simultaneous test, and partial correlation test by Lisrel 8.8. Data Analysis test with Strutural Equation Model (SEM). Research has been conducted that Resource complementarity, operational compatibility, cultural compatibility affect to interorganizational learning by R² = 75% , learning and relational capital affect to quality of knowledge transferred by R²= 74%, also resource complementarity, operational compatibility and cultural compatibility affect to relational capital by R² = 67%, that all is significant 0.05.